2006
DOI: 10.1111/j.1540-8191.2006.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Analysis of Nonelective Coronary Artery Bypass Graft Surgery

Abstract: Patients undergoing nonelective CABG have longer LOS and higher costs than patients undergoing elective CABG. The increased cost among nonelective patients is largely due to differences in rates of preoperative LOS, angiography, and PCI. This differential reflects increased nonsurgical costs among patients undergoing nonelective CABG rather than surgical costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…One of the reasons for higher cost was a higher prevalence of urgent cases in the EF ≤20% subgroup, which has been shown to carry a significantly higher cost of care. 18 Analysis of the Pennsylvania Health Care Cost Containment Council database demonstrated that higher observed to expected ratios for operative mortality were associated with increased costs. 19 Other groups also showed that increased mortality is associated with increased cost in isolated CABG.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for higher cost was a higher prevalence of urgent cases in the EF ≤20% subgroup, which has been shown to carry a significantly higher cost of care. 18 Analysis of the Pennsylvania Health Care Cost Containment Council database demonstrated that higher observed to expected ratios for operative mortality were associated with increased costs. 19 Other groups also showed that increased mortality is associated with increased cost in isolated CABG.…”
Section: Discussionmentioning
confidence: 99%
“…According to prior studies (Cota and others 2005; Ferrante and others 2015; Haider and others 2015; Kurki and others 2003; Kwok and others 2011; Violette and others 2006), index admissions were classified into four mutually exclusive groups based on the type of hospitalization: elective major surgery, non-elective major surgery, critical illness, and other. Major surgery was defined using a restricted set of International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) procedure codes for surgeries occurring in an operating room, as described in an earlier report (Kwok and others 2011).…”
Section: Methodsmentioning
confidence: 99%
“…[63][64][65][66][67][68] Although a clopidogrel washout period decreases bleeding risk, it is associated with an ϳ1% increase in reinfarction, 67,69 and increased costs because of prolonged hospital stay. 70 The ACC/AHA guidelines for both UA/NSTEMI and STEMI recommend clopidogrel cessation 5 to 7 days before CABG, unless the need for revascularization outweighs the risk of bleeding. 2,3 The recommendation to withhold clopidogrel 5 to 7 days before CABG leads many physicians to delay clopidogrel administration until after coronary angiography, which is a determinant of the need for CABG.…”
Section: Barriers To Dual Antiplatelet Therapymentioning
confidence: 99%